2012
DOI: 10.1177/1354068812462929
|View full text |Cite
|
Sign up to set email alerts
|

Out of left field? Explaining the variable electoral success of European radical left parties

Abstract: European radical left parties (RLPs) are gradually receiving greater attention. Yet, to date, what has received insufficient focus is why such parties have maintained residues of electoral support after the collapse of the USSR and why this support varies so widely. This article is the first to subject RLPs to large-n quantitative analysis, focusing on 39 parties in 34 European countries from 1990 to 2008. It uses the 'supply and demand' conceptual framework developed for radical right parties to identify a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
118
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 56 publications
8
118
2
1
Order By: Relevance
“…In the programmes of radical left-wing parties across Western Europe, we find statements such as 'Change Europe' (French Communist Party, 1999), '100% Social: No against this EU' (Dutch Socialist Party, 2014), 4 and ' Another Europe is possible' (European party group GUE/NGL, 2014). The radical left thus tends to be sceptical of the EU in its current form, while not opposing the ideal of European integration as such (March and Rommerskirchen 2012). Exceptions are a few orthodox communist parties, most notably the Greek Kommounistiko Komma Elladas (KKE) and the Portuguese Partido Comunista Português (PCP), which more fundamentally reject European integration in both its principle and practice (Charalambous 2011).…”
Section: Left-wing and Right-wing Euroscepticismmentioning
confidence: 99%
See 1 more Smart Citation
“…In the programmes of radical left-wing parties across Western Europe, we find statements such as 'Change Europe' (French Communist Party, 1999), '100% Social: No against this EU' (Dutch Socialist Party, 2014), 4 and ' Another Europe is possible' (European party group GUE/NGL, 2014). The radical left thus tends to be sceptical of the EU in its current form, while not opposing the ideal of European integration as such (March and Rommerskirchen 2012). Exceptions are a few orthodox communist parties, most notably the Greek Kommounistiko Komma Elladas (KKE) and the Portuguese Partido Comunista Português (PCP), which more fundamentally reject European integration in both its principle and practice (Charalambous 2011).…”
Section: Left-wing and Right-wing Euroscepticismmentioning
confidence: 99%
“…Most parties of the radical right categorically reject any type of integration that goes beyond the most basic economic cooperation. For most radical left-wing Eurosceptic parties, Euroscepticism constitutes a rejection of the EU's current composition and practice, rather than a principled rejection of European integration in and of itself (March and Rommerskirchen 2012).…”
mentioning
confidence: 99%
“…Radical left parties are radical in that they reject the socioeconomic structure of capitalism. They are left because they conceive of socioeconomic inequality as one of the major political challenges of our time and therefore argue that alternative economic (more redistributive) models should be introduced that redress inequality (see March & Rommerskirchen, 2015). Voters who experience economic difficulties have good reasons to feel attracted to the parties expressing such radical left messages.…”
Section: Radical Parties and Radical Votingmentioning
confidence: 99%
“…Past research for the FDG's German equivalent, Die Linke, highlighted a distinct and coherent far-left electorate consisting of economically disadvantaged groups with a strong preference for state intervention to tackle growing economic inequality (Bower and Vail, 2011). The link between economic hardship and the far-left vote has been further confirmed at the aggregate (March and Rommerskirchen, 2015) and at the individual level by Vissier et al (2014) and Bedock and Vasilopoulos (2015), who showed that social class and attitudes toward income inequality are the main explanatory factors for the rise of the far left in Europe. The few studies so far that have addressed this question focus almost exclusively on class and economic explanations.…”
Section: Introductionmentioning
confidence: 72%
“…Although, there is a number of nuances between European far-left parties (see March and Rommerskirchen, 2015) the new far left in Western Europe is ideologically characterized by a broad opposition to capitalism. During the crisis this has been mainly expressed through a strong focus on the issue of growing inequality and an opposition to the austerity policies implemented Europe wide.…”
Section: Introductionmentioning
confidence: 99%